(untitled) (GYMNASIUM, 2017)
The purpose of this study was to evaluate the low load lumbar flexion and extension exercise training on the development of isolated lumbar extension and flexion strength. Isometric torque of the isolated lumbar extension and flexion muscles was measured at two positions (0° and 30° range of motion) on 54 healthy men before and after 8 weeks of low load lumbar flexion and extension exercise training. Subjects were assigned in two groups, the first (27) trained 3 times/week with low load lumbar flexion and extension exercise and the second (control, 27) did not train. Post training isometric strength values describing isolated lumbar extension and flexion strength improved in greater extent for the low load lumbar flexion and extension exercise group in both angles (p<0.05) relative to controls. These data indicate that low load lumbar strength exercise training is an effective method of improving lumbar extension and flexion muscles strength.